The “Normative Structure” of Social Science: Merton’s Ideas as a Story of Success and Side Effects - Hillmert, Steffen (Serendipities. Journal for the Sociology and History of the Social Sciences, 2022)
Based on available literature, this essay looks at trends in scholarly attitudes and academic practices, primarily within the sphere of social sciences, and asks whether they have been in line with Robert K. Merton’s institutional principles of science as they were formulated in his famous essay “The Normative Structure of Science.” This essay argues that these principles have not been fully implemented but have become increasingly recognised and widely accepted as normative points of reference also in large parts of the social sciences. However, there have been both marked deviations and significant side effects. Given the internal heterogeneity of a discipline like sociology, practices that selectively interpret the Merton principles may add to existing internal cleavages.